A Practical Synthesis and Applications of (E)-Diphenyl-β-(trifluoromethyl)vinylsulfonium Triflate - Kasai, Noritaka; Maeda, Ryoko; Furuno, Hiroshi; Hanamoto, Takeshi (Synthesis, 2012)
(E)-Diphenyl-β-(trifluoromethyl)vinylsulfonium triflate, readily prepared from 2-bromo-3,3,3-trifluoroprop-1-ene in two steps, undergoes double alkylation with active methylene compounds in dimethyl sulfoxide or ethyl acetate, in an open vessel at room temperature, to provide the corresponding trifluoromethylated cyclopropane derivatives in excellent yields. The cyclopropane, ethyl 1-cyano-2-(trifluoromethyl)cyclopropanecarboxylate is subjected to a ring-opening reaction followed by cyclization to afford a trifluoromethylated dihydroaminothiophene, which on oxidation with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone furnishes the corresponding trifluoromethylated aminothiophene in a high 88% yield.
Keywords: vinylsulfonium salts; heterocycles; cyclization; fluorine; ylides